Characterization of QSPA plasma streams in plasma-surface interaction experiments: simulation of ITER disduption - Makhlaj, V.A. (Вопросы атомной науки и техники, 2012)
Experimental simulations of thermal stage of ITER disruptions with relevant surface heat loads (energy density up to 30 MJ/m² ) were performed with a quasi-steady-state plasma accelerator QSPA Kh-50. It was found, that the melt motion driven by plasma pressure gradient dominates in tungsten macroscopic erosion, resulting in droplet splashing and formation of the craters with rather large edge ridges of displaced material. The contribution of mass loss to surface erosion is negligible in comparison with surface profile development caused by melt motion.